The Simulation Research on the Detection of Metal Particles with Micro Planar Transformer Sensor - Liu, Bendong; Su, Yanqiang; Yang, Jiahui (Recent Patents on Mechanical Engineering, 2016)
The magnetic metal particle detection is important for health monitoring in rotating machines. In this paper, a micro planar transformer sensor for magnetic metal particle detecting is presented based on electromagnetic induction principle. The model and the simulation model of the sensor are carried out with Ansoft software. The magnetic field and the voltage of sensing coil were simulated as a paramagnetic metal particle and a diamagnetic metal particle detected by the transformer sensor respectively. The simulation results show that the magnetic field and the voltage of sensing coil are increased as the paramagnetic particle near to the sensor, however, the magnetic field and the voltage of sensing coil are decreased as the diamagnetic particle near to the sensor. The relation between the driving frequency and sensitivity of sensor is researched. The sensitivity of detection of the diamagnetic particle increases with the increase in frequency, however, the sensitivity of paramagnetic particle’s detection decreases with the increase in frequency. The paper also introduced the recent patents which are designed to detect metal magnetic particles.
Keywords: frequency selection